Проблема токсичності лазерних принтерів - Мащенко, А. Р. (ХНУРЕ, 2021)
In the given work was analyzed the dangers of using laser printers. The toxic effect of toner on humans has been studied. Suggested ways to reduce the harmful effect of laser printer toners.
Keywords: лазерний принтер; проблема токсичності